If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 + x = 5X(19 + -1x) 41 + x = (19 * 5X + -1x * 5X) 41 + x = (95X + -5xX) Solving 41 + x = 95X + -5xX Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5xX' to each side of the equation. 41 + x + 5xX = 95X + -5xX + 5xX Combine like terms: -5xX + 5xX = 0 41 + x + 5xX = 95X + 0 41 + x + 5xX = 95X Add '-41' to each side of the equation. 41 + x + -41 + 5xX = -41 + 95X Reorder the terms: 41 + -41 + x + 5xX = -41 + 95X Combine like terms: 41 + -41 = 0 0 + x + 5xX = -41 + 95X x + 5xX = -41 + 95X Reorder the terms: 41 + -95X + x + 5xX = -41 + 95X + 41 + -95X Reorder the terms: 41 + -95X + x + 5xX = -41 + 41 + 95X + -95X Combine like terms: -41 + 41 = 0 41 + -95X + x + 5xX = 0 + 95X + -95X 41 + -95X + x + 5xX = 95X + -95X Combine like terms: 95X + -95X = 0 41 + -95X + x + 5xX = 0 The solution to this equation could not be determined.
| .04x+x=1600 | | -2(2x+7)=9x | | 5/n=30/54 | | x-(-10)=30 | | 4x-2(x-3)=17+x | | -5x^2-12w+9=0 | | 2x^2+11=7 | | sqrt(w-6)=13 | | 35=6u-u | | 2(6x-3)=8x+2 | | 4x(2x^3-4x^2-x)= | | 4u+5u=27 | | -7x+37=-7+2(1-7x) | | 12u-5u=42 | | 2(x-2)-(3x-7)=3(4x-1)-7 | | -7(2-3k)=3k+40 | | 8x^4-16x^3-4x^2= | | 3y+11x= | | -9(t-2)-2(t+1)=-10 | | n^2-13n-50=0 | | 5x-(2x+3)=x-6 | | -97=-6(x+8)-7 | | 2k^2+9k=7 | | 5r^2-36r-32=0 | | 253=-2-5(7k+5) | | n^2-13n+50=0 | | -z+4=26 | | -3(8y-5)=4(1-7y)+14 | | Vf=0+0*20 | | 100x+90-x=99 | | 1+3n=1+3n | | 12+2[6+7(x+1)]=0 |